2023
DOI: 10.1002/anie.202313133
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Fluorine Groups in Passivating Defects for Perovskite Solar Cells

Xiaoqing Jiang,
Guangyue Yang,
Bingqian Zhang
et al.

Abstract: Introducing fluorine (F) groups into a passivator plays an important role in enhancing the defect passivation effect for the perovskite film, which is usually attributed to the direct interaction of F and defect states. However, the interaction between electronegative F and electron‐rich passivation groups in the same molecule, which may influence the passivation effect, is ignored. We herein report that such interactions can vary the electron cloud distribution around the passivation groups and thus changing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…XRD results were in accordance with J – V curves that the electron-rich sulfur atoms from the polymeric X22 molecule possibly react with iodine vacancies or undercoordinated lead from the perovskite film surface to enhance the obtainment chance of the maximum open-circuit voltage as well as the long-term stability of devices . For the passivation effect of the F group on Pb 2+ , reports have indicated that the F group bearing a strong electron-withdrawing property can interact with electron-rich amine passivation groups, resulting in movements of electron clouds around them toward the F groups …”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…XRD results were in accordance with J – V curves that the electron-rich sulfur atoms from the polymeric X22 molecule possibly react with iodine vacancies or undercoordinated lead from the perovskite film surface to enhance the obtainment chance of the maximum open-circuit voltage as well as the long-term stability of devices . For the passivation effect of the F group on Pb 2+ , reports have indicated that the F group bearing a strong electron-withdrawing property can interact with electron-rich amine passivation groups, resulting in movements of electron clouds around them toward the F groups …”
Section: Resultssupporting
confidence: 73%
“…58 For the passivation effect of the F group on Pb 2+ , reports have indicated that the F group bearing a strong electronwithdrawing property can interact with electron-rich amine passivation groups, resulting in movements of electron clouds around them toward the F groups. 59…”
Section: Resultsmentioning
confidence: 99%
“…Figure S1a,b shows the structure of PAAm and the density functional theory calculation result of the electrostatic potential of PAAm, respectively. The highest electron cloud density of PAAm is located at the carbonyl groups (red), indicating that carbonyl would interact with positively charged defects of the SnO 2 particle surface, such as oxygen vacancies. , We conducted Raman spectroscopy measurements to verify the interaction experimentally. SnO 2 powders obtained by lyophilization were prepared for Raman spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Organic–inorganic hybrid perovskite solar cells (PSCs) have attracted extensive attention due to their unique semiconductor properties, such as long charge carrier diffusion length, tunable bandgap, high defect tolerance, and low exciton binding energies. Within a very short time span, impressive achievements in photovoltaic applications have been made, and the certificated power conversion efficiency (PCE) of single-junction PSCs has been rapidly increased to 26.1%, which is comparable to that of Si-based solar cells. However, the poor long-term operational stability still restricts their practical application, largely because of the usage of humidity-/heat-sensitive organic methylammonium and formamidinium. Substituting organic cations with volatile-free Cs + to fabricate all-inorganic perovskites (CsPbX 3 , X = I, Br, Cl, or mixed) is an effective strategy to settle this issue. , Generally, there is a positive correlation between I doge and corresponding PCE owing to the reduced bandgap but a negative relationship for environmental stability. Although the efficiency of CsPbI 3 -based PSCs has exceeded 20%, the phase instability, which suffers from the phase conversion from the photoactive α-perovskite phase to the nonphotoactive β-perovskite phase, is still a great challenge for future deployment. ,, On the contrary, CsPbBr 3 exhibits the most superior stability, but its PCE is restricted by a narrower light-absorbing range .…”
Section: Introductionmentioning
confidence: 99%